Sunday

July 24, 2016
Posted by **James** on Saturday, December 17, 2011 at 9:15pm.

ln(x-5/x^2 - 1) - ln (x^2 - 2x -15/x + 1)

- pre calculus -
**Reiny**, Saturday, December 17, 2011 at 10:46pmln(x-5/x^2 - 1) - ln (x^2 - 2x -15/x + 1)

= ln(x-5) - ln(x^2 - 1) - (ln(x-5)(x+3) - ln(x+1) )

= ln(x-5) -( (ln (x+1) + ln(x-1) ) - ( ln(x-5) + ln(x+3) - ln(x+1) )

= ln(x-5) - ln(x+1) - ln(x-1) - ln(x-5) - ln(x+3) + ln(x+1)

= -( ln(x-1) + ln(x+3) )

= -ln( (x-1)(x+3) )

or -ln(x^2 + 2x - 3) - pre calculus -
**James**, Sunday, December 18, 2011 at 12:36amThank you!